Applying a gender lens to community fire management and peatland restoration in Indonesia - Grover, Samantha (Commonwealth Scientific and Industrial Research Organisation, 2019)
Presented by Samantha Grover (CSIRO), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.